In Vitro Study of the Protective Effects of Hydroalcholic Extract of Soybean against Impact of Oxidative Damage on Osteogenesis and Chondrogenesis of Mouse Limb Bud - Zahra Vojdani; Zahra Khodabandeh; Tahereh Talaei-Khozani (Negah Institute for Scientific Communication, 2013)
Introduction: Oxidative stress has been implicated in the pathogenesis of various diseases affecting chondrogenesis or the function of articular cartilage. The purpose of the present study was to find the effect of soybean extract on reduction of detoriation effects of oxidativestress in embryonic chondrogenesis in vitro. Methods: In order to separate ectoderm from mesenchyme, the limb buds of mouse embryos (12- 13days) removed and incubated in dispase. After separation, the limb bud rinsed and incubated in the trypsin. Adding culture media (DMEM/F12 contain 10% FBS) and pipetting, the limb buds were dissociated. The number of the cells adjusted to 1-2 ×107/mL. Superconfluent micro mass spotting of cell suspension in 96 well tissue culture plate were formed. After incubation for 1.5-2 h at 37 ºC and 5% CO2, the plate flooded with culture media. At day 5, different concentration of H2O2 and soybean extract added to fresh media and in order to induce oxidative stress, incubated for 24h. The cultures were stained with alcian blue to prove the cartilage Differentiation and alizarin red for calcium deposit. Results: The results indicated that cell viability diminished by extract and H2O2 administration although, the supplementation of the cells exposed to the oxidative stress with the extract improved cell proliferation rate. The soybean also improved the ossification and chondrification of the cells exposed to H2O2. Conclusion: The study demonstrated that soybean extract can reduce the effect of oxidative stress in embryonic chondrogenesis.